Rescuing the Jews in Lithuania during World War II: Practices of Creating a Lithuanian Museum Narrative - Šermukšnytė, Rūta (Lietuvos istorijos studijos, 2023)
Lithuanian historiography shows that the topic of rescuing the Jews in Lithuania during World War II (WWII) is intertwined into different narrative schemes: the pre-Holocaust story of the rescue of Jewish refugees at the beginning of WWII and the topic of the Holocaust in Lithuania. The question is: what narrative schemes of the rescue of the Jews are used in Lithuanian museums, what does the museum want to communicate to the public on the topic of the rescue of the Jews, by what means does the museum create a historical narrative, what historical cultural events promote the emergence of themes of the rescue of the Jews in one or another Lithuanian museum? The analysis of four cases (Vilna Gaon Museum of Jewish History, ‘Sugihara House’ in Kaunas, The Ninth Fort of Kaunas, ‘Lost Shtetl’ museum under construction in Šeduva) is used to answer these questions. It revealed that the aim of the topic of rescuing the Jews is to present the most objective, all-encompassing image of this past and to perform several important functions with the help of it. This is the education of Lithuanian and foreign visitors (the museum as a space of knowledge), honoring, remembering and thanking the Jewish saviors (the museum as a memorial space), refuting stereotypes related to the rescue of Jews (the museum as a space of demythification).
Keywords: Rescuing the Jews; World War II; Holocaust; Lithuanian museums; exhibition